Questioning the universe : concepts in physics - Sadoff, Ahren (Chapman and Hall/CRC, 2008)
WINNER 2009 CHOICE AWARD OUTSTANDING ACADEMIC TITLE! The typical introduction to physics leaves readers with the impression that physics is about 30 different, unconnected topics such as motion, forces, gravity, electricity, light, heat, energy, and atoms. More often than not, these readers are left to conclude that physics is mostly about boring, lifeless numbers. Questioning the Universe: Concepts in Physics offers the nonscientist an alternative view: one that demonstrates how physics is perpetually evolving and shows how so many seemingly diverse concepts are intimately connected. In fact, one could argue that the most important ideas in modern physics are all about unification, and that these ideas are as fascinating as they are elegant.